Association of the newly proposed dietary index for gut microbiota and hyperlipidemia: From the 2007–2020 NHANES study - Shi, Fachao; Yang, Da; Sun, Quanquan; Fang, Caoyang (PloS one, 2025)
The purpose of this study was to investigate the relationship between the Dietary Index for Gut Microbiota (DI-GM) and hyperlipidemia (HL). The DI-GM, a novel index for assessing gut microbiota diversity, has not yet been thoroughly examined in relation to HL. This research involved a cohort of 13,529 individuals enrolled from the National Health and Nutrition Examination Survey (NHANES) between 2007 and 2020. We applied restricted cubic spline (RCS) analysis and weighted multivariable logistic regression to assess the association between DI-GM and HL, supplemented by subgroup analyses to reinforce these findings. After multivariable adjustment, subjects with high intake of DI-GM were determined to have a significant reduced risk for developing HL, with a 5% reduced risk for HL for each one standard deviation increased in DI-GM (P = 0.01). In contrast with the group with a DI-GM < 3, HL in the group with a DI-GM > 6 was 40% reduced (P < 0.001). RCS analysis showed a negative linear dose-response relation between DI-GM and development of HL. Subgroup analysis showed an interaction between age-stratification and DI-GM (P = 0.01), but not with gender, racial, BMI, diabetes, and hypertension groups (P > 0.05). Our study results show a significant negative linear correlation between DI-GM and HL. However, further research is needed to confirm our findings.